2001
DOI: 10.1051/0004-6361:20000283
|View full text |Cite
|
Sign up to set email alerts
|

Crab pulsar photometry and the signature of free precession

Abstract: Abstract. Optical photometry for the pulsar PSR 0531+21 has been extended with new observations that strengthen evidence for a previously observed 60 s periodicity. This period is found to be increasing with time at approximately the same rate as the rotational period of the pulsar. The observed period and its time dependence fit a simple free precession model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…Ulmer et al (1994) reported that the intensity ratio of the two peaks in the gamma‐ray pulse of the Crab seems to vary sinusoidally with a period of ≈14 yr in both the 50–500 keV and 50 MeV bands (but not in the optical). However, the 14‐yr period differs from that observed by Lyne et al (1988) and a 60‐s modulation of the Crab’s optical pulses found by Čadež et al (1997).…”
Section: Application To Observationscontrasting
confidence: 69%
See 1 more Smart Citation
“…Ulmer et al (1994) reported that the intensity ratio of the two peaks in the gamma‐ray pulse of the Crab seems to vary sinusoidally with a period of ≈14 yr in both the 50–500 keV and 50 MeV bands (but not in the optical). However, the 14‐yr period differs from that observed by Lyne et al (1988) and a 60‐s modulation of the Crab’s optical pulses found by Čadež et al (1997).…”
Section: Application To Observationscontrasting
confidence: 69%
“…Tentative reports also exist of oscillatory variations in Crab and Vela timing residuals (e.g. Lyne, Pritchard & Smith 1988; McCulloch et al 1990; Čadež, Galičič & Calvani 1997), and some authors have inferred changes in α on the braking time‐scale from braking‐index measurements (Allen & Horvath 1997; Link & Epstein 1997) and the evolution of pulsar radio beam statistics (Tauris & Manchester 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Optical photometry of PSR 0531+21 over the last seven years [19] have confirmed the existence of variations of the pulsar emission with a period of ∼60 s. The observed period and its time dependence agree well with a free-precession model. Along with the short-period variations, analysis of observations of PSR 0531+021 has revealed longterm, quasi-periodic oscillations with a period of 15 to 30 months [10].…”
Section: Monitoring Of Pulsarssupporting
confidence: 67%
“…More recently, evidence has been presented for a 60‐s modulation in the Crab pulsar's amplitude and phase residual, both in the optical band (Čadež & Galičič 1996a,b; Čadež, Galičič & Calvini 1997). This is by far the shortest free precession period to have been proposed in the literature.…”
Section: Analysis Of Observations Of Free Precessionmentioning
confidence: 99%